Power in Sibling Conflict during Early and Middle Childhood. Issue 4 (11th March 2013) - Abuhatoum, Shireen; Howe, Nina
Abstract Sources of power children use in sibling conflict during early and middle childhood were examined according to French and Raven's typology of power. Participants included 66 dyads with an older (M = 81.8 months, SD = 14.48 months) and younger (M = 56.2 months, SD = 13.03 months) sibling. Data based upon naturalistic observations were coded for conflict issues (object, procedure, and information), power types (coercive, information, and legitimate), power effectiveness (attempts and successes), and resolutions (win/lose and compromise). Siblings used coercive power in object issues and information power in procedural issues. Whereas younger siblings used legitimate power in procedural and object issues including win/lose and compromise outcomes, older siblings used coercive power in win/lose resolutions. Siblings did not differ in their effectiveness of power, but they were most effective when coercive power was employed. Findings are discussed in light of power theory and the development of conflict management skills.